(untitled) (TANMIYAT AL-RAFIDAIN, 2025)
The current study aims to identify the factors that influence the acceptance of using social media in blended learning among students at the University of Mosul, based on established theories. The factors derived from the Theory of Reasoned Action (TRA) were represented by subjective norms, while the factors of the Technology Acceptance Model (TAM) were represented by perceived usefulness, perceived ease of use, and behavioral intention. Self-efficacy was drawn from Social Cognitive Theory (SCT), and facilitating conditions were drawn from the Unified Theory of Acceptance and Use of Technology (UTAUT). The factors of Constructivist Theory (CT) were represented by collaboration and interaction. Together, these factors—subjective norms, perceived usefulness, perceived ease of use, self-efficacy, facilitating conditions, collaboration, and interaction—constituted the variables influencing the behavioral intention to use social media in blended learning. The study adopted the descriptive-analytical approach and used an electronic questionnaire as the tool for data collection, with a sample of 305 respondents from the University of Mosul students. The study concluded that there is a clear effect of the factors related to the use of social media in blended learning—according to the technological acceptance theories (TRA, TAM, SCT, UTAUT, CT)—on the intention to accept its use among the study sample at the University of Mosul. The strongest effect was found for perceived ease of use, followed by collaboration and interaction, and subjective norms, in influencing the intention to accept the use of social media in blended learning.The study suggested the need for further research and conferences to raise awareness about the use of social media in blended learning, highlighting the importance and advantages of this technology, in order to encourage University of Mosul students to accept its use in blended learning and promote its adoption within the university.